2020
DOI: 10.1016/j.ceca.2019.102142
|View full text |Cite
|
Sign up to set email alerts
|

The emerging link between IP3 receptor turnover and Hereditary Spastic Paraplegia

Abstract: IP 3 receptor turnover is mediated by the ubiquitin ligase RNF170, which is recruited to active IP 3 receptors by the erlin1/2 complex. A new study by Wagner et al (Nat Commun, 2019) links four cases of Hereditary Spastic Paraplegia to inactivating mutations in RNF170. This increases the number of examples of mutations to the erlin1/2 complex-RNF170 module underlying neurodegenerative disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…This adaptive mechanism in response to persistent activation of IP3‐dependent signaling pathways appears particularly important in certain tissues, such as in the central nervous system. Consistently, mutations in IP3R, Erlins, and RNF170 are associated with neurological disorders such as spastic paraplegias (Gao & Wojcikiewicz, 2020). Thus, the degradation of IP3Rs may offer another example of how ERAD impacts on organelle contact sites.…”
Section: Introductionmentioning
confidence: 88%
“…This adaptive mechanism in response to persistent activation of IP3‐dependent signaling pathways appears particularly important in certain tissues, such as in the central nervous system. Consistently, mutations in IP3R, Erlins, and RNF170 are associated with neurological disorders such as spastic paraplegias (Gao & Wojcikiewicz, 2020). Thus, the degradation of IP3Rs may offer another example of how ERAD impacts on organelle contact sites.…”
Section: Introductionmentioning
confidence: 88%
“…ERLIN1 and ERLIN2 help regulate lipid metabolism and are associated with ER membrane structure and organization 208 . Moreover, the primary function of ERLINs in the ERAD pathway is to help facilitate the recognition and degradation of misfolded or unassembled proteins by serving as scaffolds that help bring together the E3 ubiquitin ligase, target protein and proteasome 209–211 . Only few have investigated the role of ERLINs in ERAD pathway; however, the studies involving conditional knockout of ERLIN1 and ERLIN2 in adult mice have shown that both genes play a critical role in regulating lipid metabolism in tissues like the liver 163 .…”
Section: Human Phenotypes and Animal And Cellular Disease Models Asso...mentioning
confidence: 99%
“…208 Moreover, the primary function of ERLINs in the ERAD pathway is to help facilitate the recognition and degradation of misfolded or unassembled proteins by serving as scaffolds that help bring together the E3 ubiquitin ligase, target protein and proteasome. [209][210][211] Only few have investigated the role of ERLINs in ERAD pathway; however, the studies involving conditional knockout of ERLIN1 and ERLIN2 in adult mice have shown that both genes play a critical role in regulating lipid metabolism in tissues like the liver. 163 Homozygous mutations in ERLIN1 gene have been identified in patients with motor disability (such as walking difficulties) but with normal brain MRI and cognition.…”
Section: E3 Ubiquitin Ligase Accessory Proteinsmentioning
confidence: 99%
“…The large luminal domains of ERLINs function in substrate recognition by interacting with specific loops of the IP3Rs. The mechanisms of IP3R regulation by the RNF170/ERLIN should be further investigated but mutations in RNF170, ERLINs, and IP3R itself are strongly associated with neurological disorders, such as ataxias and spastic paraplegias (Gao and Wojcikiewicz 2020).…”
Section: Rnf170mentioning
confidence: 99%
“…In particular, the degradation of sterol biosynthetic enzymes revealed a central role of ERAD in sterol homeostasis that is conserved from yeast to man, a topic that is discussed in Jo and DeBose-Boyd (2022). Moreover, ERAD controls the abundance of active calcium channels such as the IP3R (inositol-3 phosphate receptor), influencing cellular ion homeostasis (Gao and Wojcikiewicz 2020). Organelle contacts, specifically the contact sites between the ER and mitochondria, were recently shown to be controlled by ERAD (Zhou et al 2020).…”
mentioning
confidence: 99%